Pseudotumor Cerebri and Glymphatic Dysfunction - Bezerra, Marcio Luciano de Souza; Ferreira, Ana Carolina Andorinho de Freitas; de Oliveira-Souza, Ricardo (Frontiers in Neurology, 2018)
In contrast to virtually all organ systems of the body, until recently the central nervous system was believed to be devoid of a lymphatic system. The demonstration of a complex system of paravascular channels formed by the endfeet of astroglial cells ultimately draining into the venous sinuses has radically changed this idea. The system is subsidized by the recirculation of cerebrospinal fluid (CSF) through the brain parenchyma along paravascular spaces (PVS) and by exchanges with the interstitial fluid (IF). Aquaporin-4 channels are the chief transporters of water through these compartments. The present article hypothesizes that glymphatic dysfunction a major pathogenetic mechanism underpinning idiopathic intracranial hypertension (IIH). The rationale for the hypothesis springs from MRI studies, which have shown many signs related to IIH without evidence of overproduction of CSF. We propose that diffuse retention of IF is a direct consequence of an imbalance of glymphatic flow. This imbalance, in turn, may result from an augmented flow from the arterial PVS into the IF, by impaired outflow of the IF into the paravenous spaces, or both. Our hypothesis is supported by the facts that (i) visual loss, one of the main complications of IIH, is secondary to the impaired drainage of the optic nerve, a nerve richly surrounded by water channels and with a long extracranial course in its meningeal sheath; (ii) there is a the high association between IIH and obesity, a condition related to paravascular inflammation and lymphatic disturbance, and (iii) glymphatic dysfunction has been related to the deposition of β-amyloid in Alzheimer’s disease. We conclude that the concept of glymphatic dysfunction provides a new perspective for understanding the pathophysiology of IIH; it may likewise entice the development of novel therapeutic approaches aiming at enhancing the flow between the CSF, the glymphatic system and the dural sinuses.